AGE-RELATED FEATURES OF LIVER CHANGES DURING INTERMITTENT FASTING (LITERATURE REVIEW) - Kryvozub, Dmytro; Riabenko, Tetiana; Ponyrko, Alina (Eastern Ukrainian Medical Journal, 2025)
The increase in average life expectancy in the world and the corresponding increase in the prevalence of age-related diseases make it necessary for modern medicine to seek new approaches to their prevention and treatment. Intermittent fasting (IF) can be proposed as an effective method not only for weight loss and treatment of metabolic diseases, but also for maintaining the healthy state of internal organs, particularly the liver, during aging.Materials and methods. An analysis of literary sources was conducted to investigate modern ideas about the role of various IF methods in maintaining a healthy liver in people of different age groups.Results. Aging of liver tissue is accompanied by the gradual development of steatosis and fibrosis, which, under certain living conditions, nutrition, and the presence of metabolic disorders, leads to the development of chronic liver diseases.Intermittent fasting is based on various schemes of alternating fasting and meal times, which lead to the following changes in liver metabolism: activation of signaling pathways of the adaptive cellular response to stress, which improve mitochondrial function; glucose regulation, DNA repair, increased stress resistance, activation of lipophagy in hepatocytes, suppression of inflammation, and increased regulation of autophagy. IF has protective and rejuvenating effects and improves the functionality and composition of biomolecules, which are responsible for homeostatic, energetic, and remodeling processes in liver cells.Conclusions. IF is an effective and affordable method of non-drug treatment of metabolic diseases through the restoration and rejuvenation of the main metabolic organ of the body – the liver. The positive effect of IF on liver metabolic processes is to reduce body weight, decrease blood pressure and the level of inflammatory markers in the body, improve insulin resistance and lipid profile, and slow down aging processes. IF helps reduce the risk of developing diseases such as type 2 diabetes, non-alcoholic fatty liver disease, cardiovascular disease, and certain types of cancer, and improves the body's metabolic health. IF is a promising and relevant direction in combating the effects of liver aging, which opens up new opportunities for maintaining health in elderly people.